The "A" Frame ... - Hughes, E. J. Edward John, 1913-2007 (University of Victoria Libraries, 2023)
A graphite drawing by E.J. Hughes showing a logging A-Frame used to vertically hoist logs. The A-Frame is mounted on a Davis raft of boomed logs surrounded by floating logs and tree covered hills in the background. A note indicates this was drawn near Beattie Anchorage on Louise Island on Cumshewa Inlet, B.C. There are some notes about colours and what things are and the drawing is signed by Hughes and dated Aug 1953. ...